Strategi Perencanaan Pendidikan Madrasah dalam Mendukung Sistem Pemerintahan Berbasis Elektronik (SPBE) - Setiyono (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes the importance of the Electronic-Based Government System (SPBE) digital platform for government organizations and in educational institutions, especially for religion-based education (madrasah). Information and communication technologies are needed to make education more accessible while raising teaching standards. Information and communication technology is intended as a system that uses ICT technology so that all stakeholders can carry out their respective tasks easily and quickly. The purpose of this research is to plan madrasah education in support of SPBE. The research methodology used in this study was to use library research. The results of this study show that the Education Management Information System (SIMP) in madrasas is very helpful in being able to increase user access to open data in a timely manner without relying on any third-party components of the current information system. An education management information system (SIMP) combines Human Resources and Information Technology tools to collect, organize, store, and provide ready-to-use access to information for use in making decisions about education programs and policies. Information such as student data, student grades, and so on is provided by an Islamic education management information system (madrasah) to assist in management, planning and monitoring processes within an organization, in addition to supporting the electronic-based government system (SPBE) program. Therefore, the cooperation of various parties is needed, such as: the government, parties engaged in education, as well as technology and information experts to implement Management Information Systems in the field of madrasah education.